Regulation of Skeletal Muscle Atrophy in Cachexia by MicroRNAs and Long Non-coding RNAs - Chen, Rui; Lei, Si; Jiang, Ting; She, Yanling; Shi, Huacai (Frontiers in Cell and Developmental Biology, 2020)
Skeletal muscle atrophy is a common complication of cachexia, characterized by progressive bodyweight loss and decreased muscle strength, and it significantly increases the risks of morbidity and mortality in the population with atrophy.Numerous complications associated with decreased muscle function can activate catabolism, reduce anabolism, and impair muscle regeneration, leading to muscle wasting. microRNAs (miRNAs) and long non-coding RNAs (lncRNAs), types of non-coding RNAs, are important for regulation of skeletal muscle development. Few studies have specifically identified the roles of miRNAs and lncRNAs in cellular or animal models of muscular atrophy during cachexia, and the pathogenesis of skeletal muscle wasting in cachexia is not entirely understood. To develop potential approaches to improve skeletal muscle mass, strength, and function, a more comprehensive understanding of the known key pathophysiological processes leading to muscular atrophy is needed. In this review, we summarize the known miRNAs, lncRNAs, and corresponding signaling pathways involved in regulating skeletal muscle atrophy in cachexia and other diseases. A comprehensive understanding of the functions and mechanisms of miRNAs and lncRNAs during skeletal muscle wasting in cachexia and other diseases will, therefore, promote therapeutic treatments for muscle atrophy.